Photoinduced one-electron oxidation of Aromatic Selenides: Effect of the structure on the reversible dimerization reaction - Bouchet, Lydia María (2018)
The photochemical one-electron oxidation of alkyl aryl selenides was studied by means of laser flash photolysis (355 nm). Quenching of the sensitizers in their excited state leads to selenide radical cation in the presence of selenium derivatives. The π-type dimer of methyl phenyl selenide radical cation was detected at 630 nm at expenses of the monomeric radical cation (530 nm). The effect of modification of the aryl and alkyl substituents was also studied, resulting that the formation of dimers depends on both, the electronic properties and steric hindrance of the substituents. Both effects, an increase in steric hindrance in the alkyl moiety or the presence of strongly electron donor groups in the aromatic substituent that stabilizes the radical cation, prevent the dimer formation.